PENGARUH DEBT TO EQUITY RATIO INVESMENT OPPORTUNITYSET DAN PROFITABILITAS TERHADAP KEBIJAKAN DEVIDEN DENGAN LIKUIDITAS SEBAGAI VARIABEL PEMODERASI (Studi Pada Sektor Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Tahun 2005-2012) (Students' Journal of Accounting and Banking, 2014)
The aim of this study is to examine the effect of the Debt to Equity Ratio,Invesment Opportunity Set and Profitability to Devidend Policy with Liquidity as a Moderating Variable.The present study used purposive sampling tecnique and sample derived from manufacturing company distributed devidend period 2005-2012. Result : DER and IOS does not significantly influence on dividend policy.ROA could significantly influence on dividend policy and likuidity could be used as moderating variable between ROA and DPR.Keywords: DER, IOS,. ROA, CR, DPR